Detection of biomarkers of acute myocardial infarction by high-throughput suspension array technology in serum sample. (January 2018) - Liu, Nan; Zheng, Fengjiao; Zheng, Xiaoling
Aim: In order to assist and support early diagnosis of acute myocardial infarction (AMI), suspension array technology was established for multiplexed, rapid and accurate measurement of AMI biomarkers in serum samples.Methodology & results: It was developed by coating AMI biomarkers on distinguishable microbeads and competing with free biomarkers for complementary antibodies. The limits of detection of three AMI biomarkers were 2.5- to 50-times lower than that of the previous methods and the working ranges were four to five orders of magnitude. Accuracy and stability also met satisfying acceptance criteria in both of the intra- and interbatch testing. The variation coefficients and relative standard deviations were all less than 10%.Conclusion: Suspension array technology is completely applicable for requirements of rapid clinical diagnosis in serum sample.